2009
DOI: 10.1128/jcm.00504-09
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Characteristics of the cagA Gene of Helicobacter pylori Strains Collected from Patients from Southern Vietnam with Gastric Cancer and Peptic Ulcer

Abstract: The pathogenesis of gastroduodenal diseases is related to the diversity of Helicobacter pylori strains. CagApositive strains are more likely to cause gastric cancer than CagA-negative strains. Based on EPIYA (GluPro-Ile-Tyr-Ala) motifs at the carboxyl terminus corresponding to phosphorylation sites, H. pylori CagA is divided into East Asian CagA and Western CagA. The former type prevails in East Asia and is more closely associated with gastric cancer. The present study used full sequences of the cagA gene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 64 publications
5
44
1
1
Order By: Relevance
“…Recent studies have shown that Western-type cagA in Japan (J-Western type) was different from that of the typical Westerntype cagA found in Western countries (39). We also reported that J-Western cagA possesses a 12-bp insertion in the cagA sequence compared to typical Western cagA strains (32).…”
Section: Fig 3 Population Structure Of Okinawa Strains Population Comentioning
confidence: 63%
“…Recent studies have shown that Western-type cagA in Japan (J-Western type) was different from that of the typical Westerntype cagA found in Western countries (39). We also reported that J-Western cagA possesses a 12-bp insertion in the cagA sequence compared to typical Western cagA strains (32).…”
Section: Fig 3 Population Structure Of Okinawa Strains Population Comentioning
confidence: 63%
“…EPIYA-C and -D serve as the primary CagA phosphorylation sites and are required for binding to SHP-2 (12). Two different combinations of these motifs have been found in two distinct geographical locations, Western CagA and Eastern CagA (13). EPIYA-A and B are conserved in both two combinations (Western and Eastern), while EPIYA-C (up to 3 repeats) is specific for Western combination, and EPIYA-D is specific for Eastern strains (14).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have detected striking geographic differences in cagA sequences (26,36,53,60,63). For example, cagA sequences in H. pylori strains from East Asia or H. pylori strains from Amerindian persons within the Amazon are phylogenetically distinct from the cagA sequences that are commonly found in H. pylori strains from Western countries (26,34,36,53).…”
mentioning
confidence: 99%
“…Interestingly, two different subtypes of cagA have been detected in Japan. One subtype (which encodes an EPIYA-D motif) closely resembles the cagA alleles found in other parts of East Asia, whereas a second subtype encodes an EPIYA-C motif, which is typically found in Western forms of CagA (26,60,63). The latter subtype has been termed a "Japanese subtype of Western CagA" and has been designated "J-Western" (26,60).…”
mentioning
confidence: 99%
See 1 more Smart Citation